Market reaction to private placement - Abu Samah, A’tiqah Rashidah; Abdul Ghani, Roseziahazni; Mohamad, Zuraida; Yusof Ali, Noorhayati (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
As public-listed companies on Bursa Malaysia make announcements, either about the new issuance of stocks or other types of announcements that convey material details, stock prices will respond positively or negatively according to the announcements made. These depend on whether the market perceives the announcements as favourable or unfavourable news.